2020
DOI: 10.1063/5.0021038
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive patterning: High-resolution electrohydrodynamic jet printing with solvents

Abstract: Advancements in 3D printing have initiated a paradigm in device fabrication. Electrohydrodynamic jet (e-jet) printing is a high-resolution 3D printing method that enables customizable patterning of thin-film structures, while reducing fabrication complexity and achieving high-resolution patterns with a wide variety of materials. However, to date, e-jet printing has focused on additive material deposition, rather than patterning through material subtraction. This work proposes displacement-based e-jet printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…While the pattern above was generated using photolithography, the approach of using printed polymers to pattern structural color is general, which opens up the possibility of integrating area-selective structural color with 3D-printing techniques. In particular, we have previously shown that electrohydrodynamic jet (e-jet) printing can be combined with AS-ALD to selectively deposit functional materials with sub-micrometer line widths (significantly below the resolution of ink-jet printing) while maintaining the sub-nanometer precision afforded by ALD in the z -direction. , We extend this approach here to demonstrate additive nanomanufacturing of structural colors.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…While the pattern above was generated using photolithography, the approach of using printed polymers to pattern structural color is general, which opens up the possibility of integrating area-selective structural color with 3D-printing techniques. In particular, we have previously shown that electrohydrodynamic jet (e-jet) printing can be combined with AS-ALD to selectively deposit functional materials with sub-micrometer line widths (significantly below the resolution of ink-jet printing) while maintaining the sub-nanometer precision afforded by ALD in the z -direction. , We extend this approach here to demonstrate additive nanomanufacturing of structural colors.…”
Section: Resultsmentioning
confidence: 86%
“…While the ability of ALD to uniformly coat the entire surface of 3D objects is desirable in many applications, in other instances, it is desirable to selectively deposit ALD films only in specific locations. This can be achieved through area-selective ALD (AS-ALD), which utilizes surface modifications to deactivate the ligand-exchange reactions between precursor molecules and surface functional groups. We have recently demonstrated that AS-ALD can be achieved using polymer inhibitors deposited by electrohydrodynamic jet (e-jet) printing. , Ink-jet printing was used recently to make multicolor prints on the same sample, but e-jet-based nano-/micro-additive manufacturing process is superior to ink-jet printing in terms of enabling (1) printing a broader range of materials such as viscous polymers, conductive nanoparticle suspensions, and biomaterials and (2) sub-micron resolution patterning in the x – y plane, which is significantly higher resolution than ink-jet processes (typically >50 μm). The combination of e-jet printing with AS-ALD enables additive nanomanufacturing with sub-100 nm resolution in the x – y plane and sub-nanometer resolution in the z -direction. Moreover, while printing processes are often limited by available ink materials, ALD can be used to deposit a versatile range of functional materials with tunable electronic, optical, and mechanical properties, including metals, metal oxides, sulfides, nitrides, and polymers (using molecular layer deposition) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure b, the subtractive-patterned PMMA profile exhibits side rims (∼40 nm in height) adjacent to the trench. This is due to a coffee-ring effect during the solvent printing, which dissolved and displaced the original polymer (∼12 nm in height) to the sides, while exposing the underlying silicon surface. …”
Section: Resultsmentioning
confidence: 99%
“…At present, the micro/nano 3D printing technologies developed mainly include: direct laser writing based on two-photon polymerization [6], micro-stereophotolithography, electrohydrodynamic jet (E-jet) printing [7], laser-induced forward transfer (LIFT) [8], focused electron beam (FEB) induced deposition [9], electrochemical deposition [10], focused-ion-beam direct writing (FIBDW) [11], and microplasma deposition [12][13][14]. The printing scales include micron scales, sub-micron scales, and nano scales.…”
Section: Introductionmentioning
confidence: 99%